2015
DOI: 10.1080/02614367.2015.1035314
|View full text |Cite
|
Sign up to set email alerts
|

A case study investigating the impact of the London 2012 Olympic and Paralympic Games on participation in two non-traditional English sports, Judo and Fencing

Abstract: - ------------------------------------------------------------------------------------------------------ AbstractThe hosting of the London 2012 Olympic and Paralympic Games (LOPG) brought with it detailed legacy plans aiming to 'Inspire a Generation'. The idea that hosting a sports megaevent will encourage the host population to engage in more physical activity (PA), is commonly used by governments to justify the large investments they made (Frawley and Cush, 2011). The aim of this research paper was to inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
33
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 15 publications
2
33
0
Order By: Relevance
“…These short term events are often utilised with the aspiration to create long-term post-event impacts for the hosting nation [2]. The hosting of the London 2012 Olympic Games not only intended to deliver a great level of sport to the host city, but also promised to provide a legacy for the years to come [3][4][5]. The term legacy refers to all 'planned and unplanned, positive and negative, intangible or tangible structures created through a sports event that remain after the event' [6].…”
Section: Introductionmentioning
confidence: 99%
“…These short term events are often utilised with the aspiration to create long-term post-event impacts for the hosting nation [2]. The hosting of the London 2012 Olympic Games not only intended to deliver a great level of sport to the host city, but also promised to provide a legacy for the years to come [3][4][5]. The term legacy refers to all 'planned and unplanned, positive and negative, intangible or tangible structures created through a sports event that remain after the event' [6].…”
Section: Introductionmentioning
confidence: 99%
“…Charlton's (2010) research into the potential impact of London 2012 stressed that community sports clubs would struggle to deliver on the participation legacies that had been set out. This was an area of focus for Pappous and Hayday (2015), who studied the impact of London 2012 on participation in fencing and judo in England and indicated that grassroots VSCs play a key role in encouraging post event participation. They have argued that communication should be improved between the head office staff of the NGB and the local clubs to help them build in a way that will allow them to capitalise on the event, for example through marketing and media (Pappous & Hayday, 2015).…”
Section: Literature Reviewmentioning
confidence: 99%
“…This was an area of focus for Pappous and Hayday (2015), who studied the impact of London 2012 on participation in fencing and judo in England and indicated that grassroots VSCs play a key role in encouraging post event participation. They have argued that communication should be improved between the head office staff of the NGB and the local clubs to help them build in a way that will allow them to capitalise on the event, for example through marketing and media (Pappous & Hayday, 2015). Therefore, when researching participation legacies our attention should certainly be directed towards VSCs and their ability to deliver on participation goals, and so this was the focus of this study.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, Paralympic Games also bear a very important message being the representative of the disability rights through integration, equality, opportunity, and non-discrimination (9).…”
Section: Introductionmentioning
confidence: 99%